The integral `int 1/(x^2 - 3x + 2) dx` has to be determined

`1/(x^2 - 3x + 2)`

= `1/(x^2 - 2x - x + 2)`

= `1/(x(x - 2) - 1(x - 2))`

= `1/((x - 1)(x - 2))`

Let `1/((x - 1)(x - 2)) = A/(x - 1) + B/(x - 2)`

=> `Ax - 2A + Bx - B = 1`

=> A + B = 0 and 2A + B = -1

=> A = -1, B = 1

`int 1/(x^2 - 3x + 2)`

= `int -1/(x - 1) + 1/(x - 2) dx`

= `-int 1/(x - 1) dx + int 1/(x - 2) dx`

= `ln(x - 2) - ln(x - 1) + C`

= `ln((x - 2)/(x - 1)) + C`

**The integral **`int 1/(x^2 - 3x + 2) dx = ln((x - 2)/(x - 1)) + C`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now